Exploring the potential: Small-scale tourism entrepreneurship in emerging markets - Yuliastuti, Hilda; Kamsariaty, Kamsariaty; Istiqaroh, Choirum Rindah; Mastuti, Dian Nur; Yosepha, Sri Yanthy; Irmadiani, Nadia Dwi; Suryawan, Ryan Firdiansyah (Goodwood Publishing, 2024)
Purpose: This study explores small-scale tourism entrepreneurship in emerging markets to uncover what drives entrepreneurs in this sector. By analyzing factors such as entrepreneurial intentions, perceived opportunities, skills, and market knowledge, this study offers insights into entrepreneurship dynamics in tourism. Research Methodology: Studying small-scale tourism entrepreneurship in emerging markets using a qualitative approach means using methods that focus on understanding the experiences, perceptions, and behaviors of individuals and organizations in the tourism industry. This method is valuable for capturing the complexity of entrepreneurial activities in these markets, where economic, social, and cultural factors significantly influence the success and sustainability of small-scale tourism businesses. Results: Entrepreneurial skills are crucial for success, and this study identifies the essential skills for entrepreneurs in these markets. Market knowledge is key for decision making, and this study highlights its importance in fostering sustainable entrepreneurship. Limitations: The focus on small-scale tourism entrepreneurship may overlook large-scale tourism ventures, which could also be significant drivers of economic development in emerging markets. Contributions: By combining these elements, this study offers a thorough understanding of the potential for small-scale tourism entrepreneurship in emerging markets with the goal of providing guidance for policymakers, practitioners, and aspiring entrepreneurs to stimulate industry expansion and progress. Novelty: This study explores how entrepreneurs in these markets tackle challenges and seize opportunities, highlighting their innovative strategies and their impact on local economies. Focusing on this less-explored area, this study aims to offer insights that can guide policymakers, empower entrepreneurs, and enrich academic discussions on entrepreneurship in emerging markets.